2015
DOI: 10.1016/j.eja.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A trait-based approach to crop–weed interactions

Abstract: Understanding the mechanisms of community assembly may provide evidence to improve crop manage-ment, and in particular how weeds impact on crop yields. Focussing on plant functional traits and their diversity, we analysed a crop-weed interaction study with different levels of weed species and barley cultivar diversity to assess how weed species and barley cultivars respond to competition. Pre-emption of light resources by the taller barley did not impact on the weeds, with both weeds and barley showing similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The biodiversity in NT has both positive and negative effects on nutrient acquisition, the latter because of the competition for resources. Weed control in NT is often one of the difficulties (Soane et al 2012;Melander et al 2013;Nichols et al 2015;Pakeman et al 2015) and might limit crop yield because of direct competition for light, water and nutrients (Afifi and Swanton 2011;Silva et al 2011). Although, weed abundance was not quantified in our study in 2014, weed colonization was visually more important in NT.…”
Section: Corn Roots Affected By Tillage Practicementioning
confidence: 98%
“…The biodiversity in NT has both positive and negative effects on nutrient acquisition, the latter because of the competition for resources. Weed control in NT is often one of the difficulties (Soane et al 2012;Melander et al 2013;Nichols et al 2015;Pakeman et al 2015) and might limit crop yield because of direct competition for light, water and nutrients (Afifi and Swanton 2011;Silva et al 2011). Although, weed abundance was not quantified in our study in 2014, weed colonization was visually more important in NT.…”
Section: Corn Roots Affected By Tillage Practicementioning
confidence: 98%
“…This could manifest itself in reduced weed diversity (competitive exclusion), reduced functional diversity (restriction of weeds to a smaller part of the available trait space) and/or a shift in weed traits to escape from competition (avoidance). The latter pattern was observed in a greenhouse experiment (Pakeman et al ., ) where overall plant diversity was held constant but the diversity of the barley ( Hordeum vulgare L.) crop was increased from one genotype to five, and this led to the weeds shifting to a more conservative growth form. This impact on the weed community has two consequences: it could allow for reduced inputs of herbicides if the crop mixture has a negative impact on the growth of the weed community and it has the potential to lead to loss of in‐field biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Pakeman et al () observed that crop variety in a rotation system might favor the coexistence of weed species, preventing the establishment of a dominant weed species. These authors suggest that cropping systems may be considered to be a tool in weed management treatments.…”
Section: Discussionmentioning
confidence: 93%